Com parente se negocia? Redes migratórias e o comércio transnacional em Cabo Verde - Lobo, Andréa (2018)
The ethnographies presented in the last decades about Cape Verde show that it is almost impossible to approach some thematic referring to this country without mentioning the intense migratory flows that constitute the history of the archipelago. Thus, with the first interest in analyzing another type of flow, that of transnational trade developed by Cape Verdean women, we perceived the congruence between these flows and the migratory networks, which connect Cape Verde to European countries and the United States of America. The present paper, therefore, intends to «follow» and outline some reflections on such connections, with special emphasis on the relationships between family members living at distance. Our hypothesis, based on ethnographic data, is that in this scenario, emigrant relatives are central to initiating and/or continuing the business of family members living in Cape Verde, either by sending bidões - barrels that are usually sent full of gifts and products for resale - or in the support to constitute the commercial flow, in the guarantee to have support in the trips and negotiations in foreign countries.